Multiple Uterine Surgeries: A Key Risk Factor for Uterine Rupture in Singleton Pregnancy - Xiaoying Xu; Ye Xu; Ye Shen; Wenjun Song (Clinical and Experimental Obstetrics & Gynecology)
Background: Uterine rupture (UR) is a rare but severe obstetric complication that significantly affects maternal and neonatal health. Despite extensive ongoing research on UR risk factors, controlling for confounding variables remains crucial to ensure accurate risk assessment and the development of effective preventive measures. Therefore, this study aimed to explore the potential risk factors for UR during pregnancy to improve preventive measures and therapeutic strategies. Methods: A retrospective analysis was conducted on medical records of pregnant women with UR from January 2019 to December 2023 across 11 hospitals in Jiangsu province, China. For comparison, a control group without UR (non-UR group) comprising twice the number of UR cases, was randomly selected from the pool of women with uncomplicated pregnancies during the same period. Subsequently, patients diagnosed with UR (UR group) were matched 1:1 with those without UR (non-UR group) based on age, body mass index, blood pressure, and adequacy of prenatal care. The association between group status and risk factors was examined using multivariable analysis. Results: Among 306,336 singleton pregnancies across 11 hospitals, 72 UR cases were identified, leading to a rupture rate of 2.4 per 10,000 deliveries. Following propensity score matching (PSM), 62 patients in the UR group were compared with 62 patients in the non-UR group. Univariate analyses revealed a significantly higher incidence of cesarean section and a history of uterine surgery history among UR patients compared to non-UR patients. Multivariable analysis identified multiple uterine surgeries as an independent risk factor for UR (odds ratio [OR]: 3.141; 95% confidence interval [CI]: 1.903–5.183; p < 0.001). Conclusions: This study emphasizes the significance of multiple uterine surgeries as a potential independent risk factor for UR. Recognizing such risk factors is pivotal for refining perinatal management strategies aimed at reducing the incidence of UR. Ultimately, this reduction can significantly enhance maternal and neonatal health outcomes.